Development and evaluation of the quality of nursing care scale for hospitalized acute respiratory infection children (QNCS-HARIC) in Indonesia - Dewi Elizadiani Suza (Prince of Songkla University, 2014)
Master of Nursing Science (Nursing Science), 2013